Customer’s Behavior Towards Fast Food Chain Working Performance:Basis for Enchance Level of Satisfaction: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Fast-food chains in the Philippines are known as a crowd favorite that has been loved bychildren and adults. Jollibee is a local fast-food giant that has more than a thousand branchesin various parts of the country and hundreds more abroad. The brand is synonymous withhearty food, celebration, and the love of family, as stated by Maya (2020). Social andeconomic causes are part of a modern human’s daily life. When there is no time left to cookand prepare food, prepared fast food turns out to be a modern, convenient way to a person’sdaily life.Data shows that the majority of the respondents are in the age group of 18-21 years old,equally divided into male and female respondents, and the majority are single. Studies showthat greeting customers with a smile affects customer behavior, as well as giving good serviceand being helpful and respectful. The price of a product or service can affect the level ofsatisfaction among customers because it has an associated sense of fairness. A customer’sperceptions of unfair pricing lead to negative outcomes, such as Quality of food. The taste ofthe product will also affect the customer's tongue because all people have different tasteswhen it comes to food.The work performance of the employees or staff affects the customers' behavior and theirsatisfaction. How the employees interact with their guests will create an impact on how theywill be served back. This study recommends various ways to enhance the level of satisfactioncustomers get, especially in the fast-food industry.
Keywords: Business